SPECIFIC FEATURES OF KAZAKHSTAN-BELARUS RELATIONS IN POLITICS, ECONOMICS AND CULTURE - BURNASHEV, Igor (CENTRAL ASIA AND THE CAUCASUS, 2004)
The attainment of independence by Kazakhstan and Belarus, their political makeup, reference point and priorities attract ever greater interest, because the political course of these countries, considering their strategic position (Kazakhstan lies at the center of Asia, and Belarus at the center of Europe), is crucial to the future of the modern world, to its order and equilibrium. Belarus and Kazakhstan almost simultaneously renounced the formidable nuclear heritage of the former U.S.S.R. and are working consistently for a secure peace in adjacent regions: Kazakhstan, by calling a Conference on Cooperation and Confidence-Building Measures in Asia (CCCBMA), and Belarus, by proposing the creation of a nuclear-free zone in Eastern and Central Europe. This proposal of the Minsk authorities is one of the alternatives to NATO’s military and nuclear expansion to the east and could become an instrument for preventing the deployment of nuclear weapons in the wide corridor between the nuclear arsenals of Russia and the North Atlantic alliance. Such policies are a natural choice for countries that have suffered from nuclear tests. The two republics have a common economic past: in the days of the U.S.S.R., Kazakhstan for decades remained a raw materials appendage of the Center, while Belarus was the “assembly shop” of Soviet engineering. With the breakup of the Soviet Union, when production relations were disrupted and the new sovereign post-Soviet countries were plunged into an economic crisis, each of them began looking for a way out of that crisis all on its own. But in the early 1990s the two republics were already faced with the challenge of resuming economic relations, which could only be done on the basis of integration, but this time on principles that were fundamentally different from the basic principles of the U.S.S.R. Such were the key strategic tasks on which the authorities of Kazakhstan and Belarus focused their efforts.